On a conjecture of Mergelyan - J. E. Brennan (Հայաստանի ԳԱԱ)
A solution is presented to the problem of uniform weighted polynomial approximation on bounded simply connected domains in the complex plane, that is analogous to Mergelyan's solution to the classical Bernstein problem on the real line.
Keywords: Science; Mathematics